2010
DOI: 10.1002/jms.1731
|View full text |Cite
|
Sign up to set email alerts
|

Hydride transfer reactions via ion–neutral complex: fragmentation of protonated N‐benzylpiperidines and protonated N‐benzylpiperazines in mass spectrometry

Abstract: An ion-neutral complex (INC)-mediated hydride transfer reaction was observed in the fragmentation of protonated N-benzylpiperidines and protonated N-benzylpiperazines in electrospray ionization mass spectrometry. Upon protonation at the nitrogen atom, these compounds initially dissociated to an INC consisting of [RC(6)H(4)CH(2)](+) (R = substituent) and piperidine or piperazine. Although this INC was unstable, it did exist and was supported by both experiments and density functional theory (DFT) calculations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 69 publications
(27 reference statements)
3
71
0
1
Order By: Relevance
“…The ionic and neutral components of an INC show reactivities similar to those expected for the isolated species in the bimolecular reactions. In previous studies, we found dissociation of protonated N-benzyl amines gave rise to [benzyl cation/amine] complex and then nucleophilic aromatic substitution [8], electron transfer [23], or hydride transfer [24] could occur within the complex in different cases. In the present study, we systematically investigated the gas-phase reactions of benzyl cations with neutral N-containing species through INC intermediates in collision-induced dissociation of N-benzylated cations in ESI-MS. With these efforts, we try to figure out a more integrated landscape of the gas-phase reactivity of benzyl cations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ionic and neutral components of an INC show reactivities similar to those expected for the isolated species in the bimolecular reactions. In previous studies, we found dissociation of protonated N-benzyl amines gave rise to [benzyl cation/amine] complex and then nucleophilic aromatic substitution [8], electron transfer [23], or hydride transfer [24] could occur within the complex in different cases. In the present study, we systematically investigated the gas-phase reactions of benzyl cations with neutral N-containing species through INC intermediates in collision-induced dissociation of N-benzylated cations in ESI-MS. With these efforts, we try to figure out a more integrated landscape of the gas-phase reactivity of benzyl cations.…”
Section: Introductionmentioning
confidence: 99%
“…In electrospray ionization mass spectrometry (ESI-MS), fragmentation of benzylated cations prefers to generate benzyl cations [7,8,[20][21][22][23][24][25][26][27][28][29][30], though a few exceptions have been reported that tropylium ion can be co-produced in the fragmentation of benzylpyridinium ions [18,31,32]. Besides the formation of benzyl cations, other interesting ions resulting from hydride transfer [24,25] or electrophilic aromatic substitution reactions [20][21][22] via the nonconventional ion/neutral complex (INC) can also be generated in the dissociation of benzylated cations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sum of the free energy of the separated 2-methoxy-4-carboxylate-phenoxyl and nitrobenzyl radicals is higher than that of 1-INC-t by 24.7 kJ/mol; this indicates that 1-INC-t is relatively stable. INC is an important intermediate in gasphase chemistry, and various chemical reactions can occur between the two species or in the ionic fragment alone prior to its final separation [6,8,17,[19][20][21][22][23][24]. In addition to direct separation to Figure 5S).…”
Section: Gas-phase Decarboxylative Coupling Reactions Were Explored Bmentioning
confidence: 99%
“…Accordingly, a mechanism allowing consecutive elimination of ammonia and water could be proposed in the case of α-Glu-5A. As depicted in Scheme 2a with dashed arrows, an anchimerically-assisted process [37][38][39][40][41], occurring here via a nucleophilic attack of one oxygen atom from the acrylate moiety in C1 onto the carbonyl carbon of the acrylate group in C2 would allow elimination of NH 3 from the precursor ion to produce a stable m/z 451.1 fragment. The newly created OH group in this product ion would further be eliminated as a water molecule upon a 1,6-proton transfer, yielding the m/z 433.1 product ion.…”
Section: Cid Of [Glu-na + Nh 4 ]mentioning
confidence: 99%